The impact of environmental pollution on mental health: A comparative study between urban and rural students - Tariq Hussein Allwan Bilal; Hameed Mousa Elaf; Tariq Battal Zahraa; Hindy Tayseer; Jundi Rami (E3S Web of Conferences)
The environment and its issues have become of great importance, with environmental concerns imposing themselves on various levels, whether local, regional, or international. Environmental pollution and its risks are not confined to the borders of the country responsible for it but extend to affect other nations as well. This has encouraged countries to hold conferences and seminars to establish laws aimed at reducing this growing threat, which endangers all living beings, including humans, who are the primary cause of these problems. Environmental pollution is considered one of the most pressing issues of the modern era, threatening all nations. Iraq, in particular, has not been isolated from this pollution. Moreover, the wars, economic sanctions, and the complete collapse of infrastructure have worsened the situation, leaving negative impacts on the Iraqi environment. This research aims to examine the impact of environmental pollution on mental health through a comparative study between students in urban and rural areas.